The Impact of Project Based Learning Model with Articulate Storyline on Decimal Numbers Learning Outcomes of Students - I Putu Suardipa; Trisniawati; Nirmayani, L. Heny; Ariyana, I Komang Sesara; Yudiana, I Kadek Edi (Universitas Pendidikan Ganesha, 2025)
The research was motivated by the problem that students' mathematics learning outcomes, particularly in decimal number topics, remain unsatisfactory due to monotonous learning models and low engagement. This study was conducted to analyze whether there is a significant effect between students who receive treatment through the Articulate Storyline Assisted PjBL model and students who receive treatment through the conventional PjBL model. This quasi-experimental study used a pre-test post-test control group design and involved 186 fourth-grade students from elementary schools in Banjar District. Random sampling was applied to select 27 students from Grade IV Elementary School as the experimental group, and 15 students from Grade IV B of Banjar 2 Elementary School as the control group. Data collection techniques included observation, interviews, tests, and documentation. Statistical analysis using the t-test revealed that among the 32 students tested, the calculated t-value was 7.074, while the t-table value was 1.683. Therefore, it can be concluded that H₀ is rejected and H₁ is accepted, indicating a significant difference between the two groups.